Analisis Pengaruh Persaingan, Lokasi, Proses dan Fasilitas Terhadap Pemasaran Perumahan - Ragil Sunahar; Syofian; Veny Puspita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze the influence of competition, location, process and facilities on purchasing decisions for Housing PT Hunian Semarak Sejahtera Bengkulu City. The population in this study were all consumers who bought PT. The sample in this research is 128 samples. The nature of the research used is descriptive quantitative and the sampling method used in this research is purposive sampling method. The data used in this study are primary data and secondary data. The data analysis method used in this study is multiple regression analysis with the help of the IBM SPSS application program. The results of the analysis show that (1) the competitive variable influences the purchasing decision, (2) the location variable influences the purchasing decision, (3) the process variable influences the purchasing decision, (4) the facility variable influences the purchasing decision, (5) competition, location , Process and Facilities influence simultaneously on purchasing decisions.